UHPC-PINN-parallel micro element system for the local bond stress-slip model subjected to monotonic loading - Ahad Amini Pishro; Zhengrui, Zhang; Mojdeh Amini Pishro; Xiong, Feng; Zhang, Lili; Yang, Qihong; Siti Jahara Matlan (Elsevier Ltd, 2022)
<Please refer to the enclosed abstract>